1993
DOI: 10.1080/08964289.1993.9935179
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Crying, Depressed Mood, and Secretory Immunoglobulin A

Abstract: The relationship between emotional crying and secretory immunoglobulin A (S-IgA) in whole saliva was examined. Previous research had indicated that lower S-IgA was associated with crying. Similar results were found in the present study. Depressed mood was not associated with S-IgA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Labott et al [11] found that participants' SIgA concentrations decreased as they released their negative emotions by crying after watching a sad video. However, Martin et al [12] found no evidence for changes of SIgA if participants cried while watching a sad video. In a study by Yang et al [13] , the researchers found that negative emotion pictures could lead to an apparent negative emotional reaction among the participants without any accompanying SIgA changes.…”
mentioning
confidence: 97%
“…Labott et al [11] found that participants' SIgA concentrations decreased as they released their negative emotions by crying after watching a sad video. However, Martin et al [12] found no evidence for changes of SIgA if participants cried while watching a sad video. In a study by Yang et al [13] , the researchers found that negative emotion pictures could lead to an apparent negative emotional reaction among the participants without any accompanying SIgA changes.…”
mentioning
confidence: 97%
“…Sense of humor, as assessed by the Coping Humor Questionnaire (Martin and Lefcourt, 1983), was not associated with initial or baseline s-IgA concentration values. To examine further the effects of emotional crying on s-IgA concentration, Martin et al (1993) showed 42 undergraduates a sad movie. An increase was seen in s-IgA from pre-to postmovie in subjects who reported that they had not cried during the movie.…”
Section: Sense Of Humormentioning
confidence: 99%
“…Although one study showed that immunoglobulin titers (IgG, IgM, and IgA) were similar in depressed and healthy individuals (21) and another research demonstrate that depressed mood was not associated with secretary IgA in saliva (22). The depressed men had significantly elevated levels of the acute phase proteins, haptoglobin and alpha-1-antichymotrypsin, and of immunoglobulin G(23).…”
Section: Discussionmentioning
confidence: 99%